Steam Education in Teaching Talented Students - Rakhmonova Dilfuza Makhmudovna; Muratova Maksudovna; Sumaira Nawaz Sabina (International Journal of Inclusive and Sustainable Education, 2023)
Detailed information on the education of gifted children is given, and at the same time, ideas are also given about the role of STEAM education in the education of gifted children. A number of methods that can be used